Budaya Gerakan Masyarakat Hidup Sehat (GERMAS) sebagai Upaya Promosi Kesehatan pada Masyarakat di Kecamatan Cipayung, Kota Depok - Putri Permatasari; Agustina Agustina (Universitas Mathla'ul Anwar Banten, 2020)
GERMAS AS AN EFFORT TO PROMOTE HEALTH TO COMMUNITIES IN CIPAYUNG DISTRICT, DEPOK CITY. Strengthening health promotion and disease prevention efforts will provide extraordinary benefits. Health promotion and disease prevention are the main investments to reduce the burden on the state in financing public health services. Developing countries feel this burden due to budget constraints and the threat of budget sustainability, especially non-communicable diseases that require expensive and long-term treatment. Therefore, the Indonesian government launched the Healthy Living Community Movement (GERMAS), in the form of efforts to promote health and prevent disease that emphasize the community as the main actor. GERMAS has six main activities, namely increasing physical activity, increasing healthy living behavior, providing healthy food and accelerating nutrition improvement, increasing prevention and early detection of disease; environmental quality improvement; and increasing education on healthy living. Therefore, to support the Healthy Living Community Movement (GERMAS), which has just been launched by the government, it is necessary to mobilize the community to familiarize healthy living in accordance with the objectives of the GERMAS program. In Cipayung Urban Village, community-based health promotion and disease prevention has not been carried out. When associated with GERMAS, it is necessary to initiate community-based health promotion and disease prevention.